Affordable ART for developing countries: a cost benefit comparison of low dose stimulation versus high dose GnRH antagonist protocol - M, Noorashikin; Ong, Fee Bee; Omar, Mohd Hashim; Mohamad Razi, Zainul-Rashid; Zainuddin, Ahmad Murad; Mohd Aris, Muhammad Shamsir; Md. Ariffin, Norsina; Chue Abdullah, Nurshaireen; Syed Mohd Nasir , Sharifah-Teh Norashikin; Abdul Hamid, Fazilah (Springer Science+Business Media, 2008)
Objective Low dose stimulation (LS) is emerging as an alternative regime in assisted reproductive technology (ART). This study aimed to compare the cost-effectiveness of LS to the high dose GnRH antagonist (Atg) regime. Methods An observational prospective study conducted at an academic infertility unit from January to June 2007. Outcome measures included the numbers of follicles, oocytes and embryos, morphological quality of oocytes and embryos, clinical pregnancy (PR) and complication rate.